Auraptene inhibits migration, invasion and metastatic behavior of human malignant glioblastoma cells: An in vitro and in silico study - Seyed Hadi Mousavi; Mohammad Jalili-Nik; Mohammad Soukhtanloo; Arash Soltani; Farzaneh Abbasinezhad-Moud; Hamid Mollazadeh; Farzaneh Shakeri; Bahram Bibak; Amirhossein Sahebkar; Amir R. Afshari (Mashhad University of Medical Sciences, 2024)
Objective: The present work examined the anti-metastatic effects of auraptene and their underlying mechanisms of action in U87 Glioblastoma multiforme (GBM) cells.Materials and Methods: To test the hypothesis, cell culture, Matrigel invasion assay, scratch wound healing assay, gelatin zymography assay, qRT-PCR, and western blot analysis were conducted.Results: At sublethal concentrations of 12.5 and 25 µg/ml, auraptene exhibited a significant reduction in cell invasion and migration of U87 cells, as assessed using scratch wound healing and Transwell tests, respectively. The qRT-PCR and zymography experiments demonstrated a significant decrease in both mRNA expression and activities of MMP-2 and MMP-9 following auraptene treatment. Western blot analysis also showed that the total protein level of MMP-2 as well as phosphorylation of crucial metastasis-related proteins, including p-JNK and p-mTOR, decreased in auraptene-treated cells. The molecular docking studies consistently demonstrated that auraptene exhibits a significant affinity towards MMP-2/-9, the ATP binding site of mTOR and JNK1/2/3.Conclusion: Auraptene effectively inhibited the migration and invasion of GBM cells. This inhibitory effect was induced by modulating specific mechanisms, including suppressing MMPs, JNK, and mTOR activities. Auraptene might serve as a potential anti-metastatic agent against malignant GBM.